Neck cooling induces blood pressure increase and peripheral vasoconstriction in healthy persons - Koehn, Julia; Wang, Ruihao; de Rojas Leal, Carmen; Kallmünzer, Bernd; Winder, Klemens; Köhrmann, Martin; Kollmar, Rainer; Schwab, Stefan; Hilz, Max-Josef (Neurological Sciences, 2020)
Introduction: Noninvasive temperature modulation by localized neck cooling might be desirable in the prehospital phase of acute hypoxic brain injuries. While combined head and neck cooling induces significant discomfort, peripheral vasoconstriction, and blood pressure increase, localized neck cooling more selectively targets blood vessels that supply the brain, spares thermal receptors of the face and skull, and might therefore cause less discomfort cardiovascular side effects compared to head- and neck cooling. The purpose of this study is to assess the effects of noninvasive selective neck cooling on cardiovascular parameters and cerebral blood flow velocity (CBFV). Methods: Eleven healthy persons (6 women, mean age 42 ± 11 years) underwent 90 min of localized dorsal and frontal neck cooling (EMCOOLS Brain.Pad™) without sedation. Before and after cooling onset, and after every 10 min of cooling, we determined rectal, tympanic, and neck skin temperatures. Before and after cooling onset, after 60- and 90-min cooling, we monitored RR intervals (RRI), systolic, diastolic blood pressures (BPsys, BPdia), laser Doppler skin blood flow (SBF) at the index finger pulp, and CBFV at the proximal middle cerebral artery (MCA). We compared values before and during cooling by analysis of variance for repeated measurements with post hoc analysis (significance: p < 0.05). Results: Neck skin temperature dropped significantly by 9.2 ± 4.5 °C (minimum after 40 min), while tympanic temperature decreased by only 0.8 ± 0.4 °C (minimum after 50 min), and rectal temperature by only 0.2 ± 0.3 °C (minimum after 60 min of cooling). Index finger SBF decreased (by 83.4 ± 126.0 PU), BPsys and BPdia increased (by 11.2 ± 13.1 mmHg and 8.0 ± 10.1 mmHg), and heart rate slowed significantly while MCA-CBFV remained unchanged during cooling. Conclusions: While localized neck cooling prominently lowered neck skin temperature, it had little effect on tympanic temperature but significantly increased BP which may have detrimental effects in patients with acute brain injuries.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Blood pressure increase; Cerebral blood flow velocity; Hypothermia; Neck cooling